Ligand-responsive upregulation of 3′ CITE-mediated translation in a wheat germ cell-free expression system. Issue 2 (15th December 2016) - Ogawa, Atsushi; Murashige, Yuta; Tabuchi, Junichiro; Omatsu, Taiki
Abstract : We rationally designed a novel regulation-type of artificial riboswitch that upregulates the 3′ CITE-mediated translation in response to a specific ligand without major hybridization switches in a plant expression system. Abstract : We have rationally constructed a novel regulation-type of artificial riboswitch that ligand-dose dependently upregulates translation initiation mediated by a 3′ cap-independent translation element (3′ CITE) with no major hybridization switches in a plant expression system (wheat germ extract).